Assessing the effects of Children's independent mobility range and time. (December 2020) - Bagheri, Hossein; Zarghami, Esmeail
Abstract: Introduction: Previous studies provide evidence that associations between different factors and children's independent mobility (CIM). In these studies, no difference between CIM range and time whereas have been difference between CIM range and time and attitudes of children and parents. Roles of different factors, including gender haven't been also proven with CIM time and range. Therefore, sought to determine impact assessment of socio-demographic, built-environmental and perceptual characteristics with CIM time and range varied by sex. Methods: The present study measured the longest distance of each child from house as CIM range (meter) and the CIM time was calculated based on the weekly activity programs of children (minutes). Research were conduct in Ilam, Iran and 102 twelve-to-fourteen-year-old children and their parent were studied (N = 204). Results: Results of multivariate regression indicated that the CIM time was affected by parents' perception and equal between girls and boys (32 min) despite the fact that parents' fear of crime against girls was higher than boys'. The CIM range was highly dependent on built-environmental characteristics and boys' CIM range (216 m) was greater than girls' (159 m). Conclusions: Vertical development of housing, parents' fear and sex differences were the most important factors in reducing the CIM. Highlights: CIM time was reduced by parents' fear. Parents' understanding of crime against girls was higher than boys. CIM time was equal between girls and boys. CIM range of boys was greater than girls. CIM range has been related to housing characteristics.